(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
For several decades, the problem of divorce has been more relevant than ever. Every year the number of divorces is growing inexorably, and the number of couples entering into legal marriage, on the contrary, is declining. Nearly half of men and women who marry end up divorcing. The consequences of the current situation are reflected both in the subsequent life of the spouses already outside of marriage, and in modern society. The level of responsibility of the population is reduced, the number of incomplete families is growing.